Evaluation of new classifications of N descriptor in non-small cell lung cancer (NSCLC) based on the number and the ratio of metastatic lymph nodes - Pawełczyk, Konrad (J Cardiothorac Surg, 2016)
BACKGROUND: The aim of the study was to evaluate the prognostic power of new classifications of N descriptor created basing on the number (NLN) and the ratio of metastatic lymph nodes (RLN) in NSCLC compared to the current classification (CLN). METHODS: The data of 529 patients with NSCLC operated with the intention of radical resection, were analyzed. The new categories of N descriptor were created as follows: 1) NLN - median number of metastatic nodes was 3, thus in NLN0 the number of metastatic nodes =0, in NLN1 1-2, in NLN2 ≥ 3, 2) RLN - median ratio (number of metastatic lymph nodes to all nodes removed) was 12.4 %, thus in RLN0 the ratio was 0, in RLN1 < 13 %, in RLN2 > 13 %. The prognostic value of each classification was calculated on the basis of hazard ratios defined in multivariate Cox proportional hazard model. RESULTS: The new classifications of N descriptor turned out to be an independent strong prognostic factor (p <0.001) with a 5-year survival rate NLN0-62 %, NLN1-39 %, NLN2-26 % and RLN0-62 %, RLN1-37 % and RLN2-26 %. For 5-year survival rates in CLN0-62 %, CLN1-42 %, CLN2-24 % (p < 0.001), a higher prognostic value of new classifications was not demonstrated, the hazard ratio amounted to 2.22, 2.08, 2.49 for NLN2, RLN2 and CLN2 respectively. CONCLUSION: Despite the significantly high prognostic power, the new classifications cannot be considered superior over CLN. There are some deficiencies in the current classification, therefore further studies on its improvement are needed.